Methodology for specifying and evaluating the thermal performance for single family houses, applied in Londrina-PR - Barbosa, Miriam Jerônimo (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This article presents the development of a methodology to specify and evaluate the thermal performance for one-floor single family houses. The structure for devising the methodology was: establishing the thermal comfort limits to be used, adjusting an hourly thermal simulation tool with field data from different building systems, and establishing the annual number of hours of discomfort to be accepted based on a reference building system. The methodology was applied in Londrina, PR, where a field work was carried out in different building typologies. The data was used to adjust the hourly thermal simulation tool and to confirm a thermal comfort limit. The number of hours of indoor temperature outside the comfort limits was defined as the number of annual hours of discomfort. Using the Thermal Reference Year (TRY) developed for Londrina, simulations were performed for several building system alternatives. A limit for the number of annual hours of discomfort was established based on the economics reality and on the reference building system. The evaluation by performance can be made by using an annual hourly simulation tool to quantify the hours of discomfort of a given building and comparing it to the established limit.